Screening and Development of New Inhibitors of FtsZ from M. Tuberculosis. - Bini Mathew; Judith Varady Hobrath; Larry Ross; Michele C Connelly; Hava Lofton; Malini Rajagopalan; R Kiplin Guy; Robert C Reynolds (PLoS ONE)
A variety of commercial analogs and a newer series of Sulindac derivatives were screened for inhibition of M. tuberculosis (Mtb) in vitro and specifically as inhibitors of the essential mycobacterial tubulin homolog, FtsZ. Due to the ease of preparing diverse analogs and a favorable in vivo pharmacokinetic and toxicity profile of a representative analog, the Sulindac scaffold may be useful for further development against Mtb with respect to in vitro bacterial growth inhibition and selective activity for Mtb FtsZ versus mammalian tubulin. Further discovery efforts will require separating reported mammalian cell activity from both antibacterial activity and inhibition of Mtb FtsZ. Modeling studies suggest that these analogs bind in a specific region of the Mtb FtsZ polymer that differs from human tubulin and, in combination with a pharmacophore model presented herein, future hybrid analogs of the reported active molecules that more efficiently bind in this pocket may improve antibacterial activity while improving other drug characteristics.